Diagnostics of Lowland Gate in Gdansk in the context of the revitalization process - Kołodziejczak, Jakub; Gołębiewski, Michał; Rucka, Magdalena (Budownictwo i Architektura / Civil and Architectural Engineering, 2013)
This paper presents the historical context, and the story of the Lowland Gate in Gdansk. The current state and present studies are discussed. The final section provides conclusions regarding the causes of poor technical condition of the Gate and opportunities to carry out activities that may improve its condition.